A set of structural features defines the cis-regulatory modules of antenna-expressed genes in Drosophila melanogaster. - Yosvany López (Public Library of Science (PLoS), 2014)
Unraveling the biological information within the regulatory region (RR) of genes has become one of the major focuses of current genomic research. It has been hypothesized that RRs of co-expressed genes share similar architecture, but to the best of our knowledge, no studies have simultaneously examined multiple structural features, such as positioning of cis-regulatory elements relative to transcription start sites and to each other, and the order and orientation of regulatory motifs, to accurately describe overall cis-regulatory structure. In our work we present an improved computational method that builds a feature collection based on all of these structural features. We demonstrate the utility of this approach by modeling the cis-regulatory modules of antenna-expressed genes in Drosophila melanogaster. Six potential antenna-related motifs were predicted initially, including three that appeared to be novel. A feature set was created with the predicted motifs, where a correlation-based filter was used to remove irrelevant features, and a genetic algorithm was designed to optimize the feature set. Finally, a set of eight highly informative structural features was obtained for the RRs of antenna-expressed genes, achieving an area under the curve of 0.841. We used these features to score all D. melanogaster RRs for potentially unknown antenna-expressed genes sharing a similar regulatory structure. Validation of our predictions with an independent RNA sequencing dataset showed that 76.7% of genes with high scoring RRs were expressed in antenna. In addition, we found that the structural features we identified are highly conserved in RRs of orthologs in other Drosophila sibling species. This approach to identify tissue-specific regulatory structures showed comparable performance to previous approaches, but also uncovered additional interesting features because it also considered the order and orientation of motifs.